PUBLIC RELATIONS OF MANAGEMENT IN CUSTOMER RELATIONSHIP MANAGEMENT PROGRAM (CRM) AT LIABILITY COMPANY OF JASA RAHARJA BRANCH RIAU - Fadila, Mike; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Public relations of management is a system or activity that regulates public relations activities. One of the PR program is the Customer Relationship Management (CRM), in order to approach the owners of public transport in order to create customer loyalty that will increase awareness and smoothness depositing dues payer. This study aims to determine the application of the management functions of planning, organizing, actuating, and controlling the program Customer Relationship Management (CRM) at liability company Branch Riau.This research used a qualitative method with descriptive approach. Subjects were four (4) people as informants through purposive technique, and 5 (people) use a snowball technique. The collection of data obtained through interviews, observation, and documentation. To achieve the validity of the data in this study, researcher used the extension of participation and triangulation.The results showed that, the implementation of the planning function on the CRM program to serve as guidelines in planning the implementation of the program next year on the objectives set, objectives of activities to be achieved, as well as define the actions to realize the goals set. The function of organizing the work of grouping formally drafted, members are responsible for higher-level supervisor. Further applied CRM program carried out by officers in Samsat, the officer responsible for the implementation of a CRM program on public vehicle owners. Implementation of the controlling function is to evaluate the implementation of a CRM program implemented officers on public transport owners, whether CRM implemented according to a predetermined plan. Keyword: program, management, customer, relationship